Design Consistency Index for Two-lane Roads based on Continuous Speed Profiles - Almeida, Raul; Vasconcelos, Luís; Bastos Silva, Ana (Promet - Traffic&Transportation, 2018)
It is well known that road accidents tend to be more frequent in locations where a sudden change in road characteristics violates the driver’s expectations. Most methods used to assess the design consistency are based on simplified speed profiles that give a coarse description of the vehicle dynamics along the road. This paper presents a new approach to quantify the road design consistency, based on continuous operating speed profiles. These profiles are based on the Gipps’ car-following equations, adapted to simulate the driver behaviour in the vicinity of horizontal curves under free-flow conditions. A methodology to calibrate and validate the Gipps’ behavioural parameters from field data is presented and applied to predict the speed profiles of three drivers for a set of rural road segments. The calibration is based on trajectory data collected with an instrumented vehicle and it follows an automated procedure that aims to minimize the differences between the predicted and observed speed profiles. The new consistency index is based on the deceleration distances and it allows to overcome some limitations of the existing methods.